Elective surgery to save my life: rethinking the "choice" in bariatric surgery. (23rd November 2016) - Trainer, Sarah; Benjamin, Tonya
Abstract: Aims: The aim of this study was to explicate the processes by which a patient's choice to undergo bariatric surgery is made to feel like a medical necessity, to explore the ways widespread societal stigmatization of weight and bariatric surgery shapes patient and provider discourse about surgery and to discuss patient rationalizations of the choice to have surgery. Background: Severe obesity is currently highly stigmatized. Bariatric surgery has become an increasingly used option for individuals seeking to lose drastic amounts of weight. The surgery itself, however, remains stigmatized across many diverse settings. Design: This research design is centred on an ethnographic study of bariatric surgery patients who undergo surgery at a particular bariatric clinic in the American Southwest. Methods: Data collection included repeated ethnographic interviews with 35 individuals enrolled in the bariatric programme over the past 5 years. The interviews were supplemented by extensive participant observation, starting in 2014 to date. Thematic analysis of fieldnotes and transcribed interviews followed. Results: People who have bariatric surgery for weight‐loss may trade one type of stigma for another. Thus, individuals who qualify for bariatric surgery based on weight alone may be reluctant to explore the surgery as a viable option. This research also shows that younger women are more likely to face the effects of weight‐related stigma, which has an impact on their motivations for undergoing bariatric surgery. Conclusion: Stigma – both weight‐related and surgery‐related – needs to be addressed at a larger level, in terms of policy and in clinical bariatric programmes.